MR Owethu Mlambo - Owethu Mlambo (N/A, 2026)
Informal economies in South Africa, specifically within the Gauteng City-Region, represent a vital but "unmeasured" economic engine. Despite their scale, these high-entropy systems suffer from a "resolution gap" in data, leading to suboptimal investment and policy-making (pp. 1-2). This paper proposes a framework for an Informal Economic Digital Twin (IEDT) to decode the inherent disorder of township economies through structured information flow (p. 1). Methodology: Using a Multi-Resolution Data Stack, the research integrates decadal census data, quarterly labour surveys (QLFS), and high-resolution ward-level indicators from the GCRO Quality of Life Survey (2024) (pp. 2-3). This data seeds an Agent-Based Model (ABM) that utilizes distributed human intelligence and Monte Carlo simulations to model agent heterogeneity and "re-order" system entropy under specific policy interventions (pp. 2, 5). Results: Preliminary findings from the Gauteng case study demonstrate that the perceived chaos of informal sectors is a measurement problem rather than a lack of structure (pp. 1, 3). The model successfully identifies "opportunity deserts" and predicts differentiated economic impacts for diverse personas, such as township entrepreneurs and NEET youth (p. 3). Conclusion: The IEDT provides a scalable "Gold Standard" for data ingestion, allowing for more efficient capital direction and risk assessment in township spaces (pp. 1, 5). This approach transforms high-entropy noise into actionable economic signals, essential for an economically inclusive South Africa (pp. 1, 4).
Keywords: InfoInformal Economic Digital Twin; Township Economy; Agent-Based Modeling (ABM) (; Information Entropy; Gauteng City-Region